2018
DOI: 10.3389/fpsyg.2018.01184
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Genuine and Deliberate Displays of Surprise in Static and Dynamic Faces

Abstract: People are good at recognizing emotions from facial expressions, but less accurate at determining the authenticity of such expressions. We investigated whether this depends upon the technique that senders use to produce deliberate expressions, and on decoders seeing these in a dynamic or static format. Senders were filmed as they experienced genuine surprise in response to a jack-in-the-box (Genuine). Other senders faked surprise with no preparation (Improvised) or after having first experienced genuine surpri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 55 publications
2
49
0
1
Order By: Relevance
“…If decoders are poor at separating emotional cue authenticity, then being emotionally perceptive may be useful for detecting genuine emotions but detrimental when attempting to detect feigned (deceptive) emotions. This is supported by findings showing senders can produce genuine-looking emotional expressions (Krumhuber & Manstead, 2009), and that decoders a poor at separating expression authenticity (Zloteanu et al, 2018).…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…If decoders are poor at separating emotional cue authenticity, then being emotionally perceptive may be useful for detecting genuine emotions but detrimental when attempting to detect feigned (deceptive) emotions. This is supported by findings showing senders can produce genuine-looking emotional expressions (Krumhuber & Manstead, 2009), and that decoders a poor at separating expression authenticity (Zloteanu et al, 2018).…”
Section: Discussionmentioning
confidence: 66%
“…reliable muscle activation). However, this is only valid if there are perceptual differences between genuine and deceptive expressions, which seems to not be the case (Krumhuber & Manstead, 2009), nor do decoders seem capable of discriminating emotion authenticity (Zloteanu et al, 2018). Liars may be able to produce deceptive emotional displays that are "good enough" to activate the genuine embodied simulation in decoders, misleading them to infer this reflects the sender's underlying affect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it has been shown that spontaneous facial actions differ in their temporal and morphological characteristics (e.g., duration, intensity, asymmetry) from posed ones [65]. Furthermore, the overall patterns of activity are often heterogeneous, which renders them more difficult to discern because of their ambiguous emotional content [66][67][68]. Results based on instructed and stereotypical facial portrayals may therefore not be directly transferable to those derived from activity occurring in spontaneous situations.…”
Section: Discussionmentioning
confidence: 99%
“…However, facial expressions can be ambiguous and nuanced. Some of them are shown in order to be polite, prevent conflicts, or strategically mask one's true intention to obtain resources that could otherwise be denied (Namba et al 2016;Zloteanu et al 2018). This is particularly true for smile expressions which occur frequently (Chapell 1997), are perceptually salient (Smith and Schyns 2009), and easy to produce on demand (Ekman and Friesen 1982;Ekman et al 1988).…”
Section: Introductionmentioning
confidence: 99%